Sources of productivity growth: An empirical analysis with German sectoral data - Werner Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1995)
In the paper, the productivity growth of German sectors is analyzed. Sectoral production functions are estimated with annual national account data of 51 sectors from 1960-1990. Both, the pure Solow growth model and the Solow model augmented with human capital do not account for observed productivity increases. It should be extended by allowing for inter-industry spillovers and scale economies at the aggregate level, as well as for scale economies associated with human capital at the sectoral level. The business cycle affects observed productivy changes both in the short run and in the long run.
Keywords: D24; O47; O52; 330; Endogenous growth; human capital; intersectoral spillovers; Produktivität; Wirtschaftswachstum; Humankapital; Produktionsfunktion; Deutschland